(untitled) (Zia e Tahqeeq, 2025)
Corruption is one of the social challenges faced by societies and has become an international issue for states. Corruption is the abuse of entrusted power for private gain, it erodes trust, weakens democracy, hampers economic development and further exacerbates inequality, poverty, social division, and the environmental crisis. Public management is always in pursuit of corruption control with techniques developed by different political and financial systems. Pakistani society is associated with Islamic ethical teachings and these teachings have scope to maintain financial justice through control of corruption. This article mainly addresses the act of financial corruption and its impacts on Pakistani society and provides ethical guidelines in the light of Quran and Sunnah.